Does attentional bias to threat ameliorate or exacerbate the detrimental effect of trait anxiety on behavioural preparedness for real-world danger? - Notebaert, L.; Clarke, Patrick; MacLeod, C. (John Wiley & Sons Ltd., 2016)
Objective: Heightened trait anxiety is associated with impaired behavioural preparedness for natural hazards. However, little is known about the mechanisms that contribute to this association. Research has shown that trait anxiety is associated with an attentional bias (AB) towards threat-relevant information, and some researchers have suggested that such vigilance could exacerbate the detrimental effect of trait anxiety on behavioural preparedness. Conversely, given the potentially adaptive role of AB in promoting engagement in danger mitigation behaviour, it is also possible that AB could ameliorate the negative association between anxiety and preparedness. The aim of this study was to discriminate the validity of these two hypotheses. Method: Participants were recruited from a bushfire-prone community in Western Australia and were assessed on measures of trait anxiety, AB to threat, and current bushfire preparedness. Results: As predicted, the results showed a negative correlation between trait anxiety and bushfire preparedness, and a positive correlation between trait anxiety and AB to bushfire-related threat. Furthermore, the negative relationship between trait anxiety and preparedness was moderated by this AB to bushfire-related threat, with the direction of this moderation showing that AB further exacerbated this negative relationship. Conclusions: This study is the first to show that in a situation where people are exposed to a real-world danger that can be mitigated through appropriate engagement in specific preparatory behaviours, AB to danger-relevant threat serves to strengthen the observed negative association between trait anxiety and behavioural preparedness. Implications of these findings are discussed.